1998
DOI: 10.1063/1.121965
|View full text |Cite
|
Sign up to set email alerts
|

Effects of C or Si co-implantation on the electrical activation of B atoms implanted in 4H–SiC

Abstract: The influence of co-implantation of C or Si ions on the electrical activation of B acceptors in 4H–SiC was studied by using Hall effect and photoluminescence (PL) investigations. The free hole concentration in B-implanted layers is found to increase due to co-implantation of C and to decrease owing to Si co-implantation. Hot co-implantation of C at 800 °C gives rise to a further increase of the free hole concentration. It is found that the intensity of the PL peak at a wavelength 383.9 nm, which arises from sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…The nature of the 415nm and 427nm PL features inferred by examining the spectrum depth dependence is consistent with previous results [1][2][3][4][5][6][7][8][9]. Previous studies indicated that the sharp feature at 415 nm arises from donor-acceptor pair (DAP) recombination, involving traceimpurity-level nitrogen donor and the B acceptor atoms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The nature of the 415nm and 427nm PL features inferred by examining the spectrum depth dependence is consistent with previous results [1][2][3][4][5][6][7][8][9]. Previous studies indicated that the sharp feature at 415 nm arises from donor-acceptor pair (DAP) recombination, involving traceimpurity-level nitrogen donor and the B acceptor atoms.…”
Section: Discussionsupporting
confidence: 90%
“…The as-implanted range of the lighter B atoms is greater, high temperature annealing produces greater dopant drive-in, and device reliability and performance is improved [1][2][3][4][5][6][7][8][9]. Thermal drive-in of implanted B offers several advantages over doping with other common p-type species in SiC.…”
Section: Introductionmentioning
confidence: 99%
“…While the root cause of high resistivity in SiC is not well understood, purity of the material clearly plays a role. The main residual impurities in undoped SiC are nitrogen (shallow donors) [2] and boron (shallow acceptors) [3] commonly present in the high-10 15 cm À3 -low-10 16 cm À3 concentration [4]. High resistivity is achieved by balancing these shallow impurities by deeplevel defects.…”
Section: Introductionmentioning
confidence: 98%
“…8 The origin of the deep boron level has been suggested as a boron atom on a Si site next to a C vacancy, thus forming a complex. 9 The isolated carbon vacancy is suggested to act as a deep-donor-like level. Thus, it should be taken into account as a possible compensation center in p-type 4H-SiC.…”
Section: Introductionmentioning
confidence: 99%